2007
DOI: 10.1002/lsm.20532
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic characterization of collagen modifications induced by low‐temperature diode‐laser welding of corneal tissue

Abstract: The preservation of substantially intact, undenatured collagen fibrils in laser-welded corneal wounds supported the thermodynamic studies that we carried out recently, which indicated temperatures below 66 degrees C at the weld site under laser irradiation. This observation enabled us to hypothesize that the mechanism, proposed in the literature, of unwinding of collagen triple helixes followed by fibrils "interdigitation" is not likely to occur in the welding process that we set up for the corneal suturing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 53 publications
3
33
0
Order By: Relevance
“…The process is based on the photothermal activation of the main components of the extracellular matrix: heating of the tissue induces the formation of new bonds and interactions between adjacent molecules, stabilized upon cooling [3].…”
Section: Introductionmentioning
confidence: 99%
“…The process is based on the photothermal activation of the main components of the extracellular matrix: heating of the tissue induces the formation of new bonds and interactions between adjacent molecules, stabilized upon cooling [3].…”
Section: Introductionmentioning
confidence: 99%
“…Prompted by these findings, researchers at our center developed a system combining a CO 2 laser with a fiber-optic radiometer to monitor and control the temperature of the irradiated biological tissue in real time, thus preventing photothermal damage to the cornea as well as indicating the proper surface temperature for achieving the corneal seal [17,18,19]. This real-time system enables the surgeon to halt welding when the corneal surface temperature exceeds 65°C, which was previously found to be the upper limit of the surface temperature in which there is no denaturating photothermal injury to the irradiated cornea [20]. Fibers made of polycrystalline halides are used because they are highly transparent in the mid-infrared range, unlike the standard optical fibers of a Nd:YAG laser [21].…”
Section: Introductionmentioning
confidence: 99%
“…The first step is governed by the thermal denaturation of PGs, mainly occurring before the onset of fibrillar collagen denaturation, that is, from $45 to $60 C. In this range one or two subsequent phase transitions are observed that are correlated to a local disorder of the regular fibrillar collagen arrangement. This can probably be ascribed to the breaking of interfibrillar PGs bridges, which leads to a drastic change of the interfibrillar distances [18,19]. The next stage consists in the helix-to-coil transition of collagen molecules, which proceeds in two following steps.…”
Section: Thermal Modifications Of Connective Tissues and Mechanism Ofmentioning
confidence: 99%
“…These include traditional methods such as optical and fluorescence microscopy, which allow for an investigation at the micron scale [6,24], and transmission and scanning electron microscopy (TEM and SEM, respectively), which are useful when studying nanometric structures [19,25,26]. Other techniques recently applied for the analysis of biological material have also been tested, such as atomic force microscopy (AFM) and second-harmonic generation (SHG) microscopy, which provide complementary information [27][28][29].…”
Section: Thermal Modifications Of Connective Tissues and Mechanism Ofmentioning
confidence: 99%
See 1 more Smart Citation